2020
DOI: 10.1016/j.bbrep.2020.100811
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine protects from intestinal epithelial injury by modulating butyrate uptake via upregulation of membrane monocarboxylate transporter 1 levels

Abstract: Background and aims A relationship between treatment outcomes and intestinal microbiota in patients with inflammatory bowel diseases has been demonstrated. Cyclosporine treatment leads to rapid improvement in severe ulcerative colitis. We hypothesized that the potent effects of cyclosporine would be exerted through relationships between intestinal epithelial cells (IECs) and the host microbiota. The present study was designed to elucidate the effects of cyclosporine on monocarboxylate transporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Inhibition of calcineurin protected from epithelial damage and goblet cell loss and markedly reduced leukocyte infiltrations which stabilize mucosal erosions (27). This is in line with observations that point to a direct role of calcineurin in intestinal epithelial cell death (22,23), which is critical during DSS-induced colitis (28, 29). Our histological analyses point to a more consistent abrogation of mucosal damage, epithelial dysfunction and goblet cell loss in voclosporintreated mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Inhibition of calcineurin protected from epithelial damage and goblet cell loss and markedly reduced leukocyte infiltrations which stabilize mucosal erosions (27). This is in line with observations that point to a direct role of calcineurin in intestinal epithelial cell death (22,23), which is critical during DSS-induced colitis (28, 29). Our histological analyses point to a more consistent abrogation of mucosal damage, epithelial dysfunction and goblet cell loss in voclosporintreated mice.…”
Section: Discussionsupporting
confidence: 92%
“…We chose the dextran sodium sulfate-model of acute colitis, which shares many clinical features with acute severe ulcerative colitis, especially in regard to mucosal erosions, rectal bleeding and diarrhea development. Various studies have previously described protective effects of cyclosporine A in DSS-induced colitis (22,23,26). We observed that both voclosporin and cyclosporine A strongly abrogated severe colitis in this model.…”
Section: Discussionmentioning
confidence: 99%
“…The low amount of butyrate and other abnormalities of the microbiota are speculated to contribute to the refractory disease, even if drugs suppress inflammatory cytokines and immune cells. We reported that the efficacy of cyclosporine treatment in an animal colitis model deteriorated with antibiotic pretreatment but recovered with butyrate supplementation [60]. We showed that cyclosporine treatment upregulates the expression of membrane MCT1 in IECs without inducing transcriptional changes.…”
Section: Influence Of Gut Microbiota On Response To Advanced Therapiesmentioning
confidence: 89%
“…Interestingly, some of the drugs used in psoriasis management are potent agonists of these receptors; e.g., dimethyl fumarate exhibits a high affinity to the GPR109a receptor [ 63 , 64 ]. Cyclosporine, another antipsoriatic drug, may increase the intestinal uptake of certain SCFAs, especially butyrate [ 65 ].…”
Section: Short-chain Fatty Acidsmentioning
confidence: 99%